2013
DOI: 10.4236/fns.2013.412164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trans Fatty Acid Content in Widely Consumed Snacks by Gas Chromatography in a Developing Country

Abstract: Trans fatty acids have adverse effects on health, so knowledge of their contents in foods would enable people to make informed food choices. TFA levels when not available in food composition tables make it difficult to estimate dietary intake. With the aim to analyze and identify the actual amount of trans fatty acid present in selected Indian fast food items, triplicate samples of six commonly consumed snacks as well as the oil used for preparing the same were collected from three different places. The separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…High levels of PUFA observed in several samples in this study are in contrast to some of the earlier studies. Very few foods studied by Gupta et al (2016) and none of the foods analyzed by [7,8,10,18] have reported such high PUFA content in the foods. These results thus probably indicate recent consumer preference towards the PUFA rich sources such as sunflower and soybean oils over the conventional oils [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of PUFA observed in several samples in this study are in contrast to some of the earlier studies. Very few foods studied by Gupta et al (2016) and none of the foods analyzed by [7,8,10,18] have reported such high PUFA content in the foods. These results thus probably indicate recent consumer preference towards the PUFA rich sources such as sunflower and soybean oils over the conventional oils [24].…”
Section: Resultsmentioning
confidence: 99%
“…MUFA was also depicted as the most dominant class of fatty acids (range 42.7–63.9%) in only four samples: 10, Potato Chips; 15, Chakli; 47, Papadi; and 50, Fafda, all of which were non-perishable deep-fried sample (S2 Table). Most of the earlier studies on Indian foods have also indicated that MUFA were not the most dominant types of fatty acids in these foods [4,5,7,8]. However, few other studies have shown that groundnut, canola and olive oils [2123], and some of the Cretan and Cypriot snacks [20] had highest levels of MUFA than any other fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFs of food items consumed were calculated according to the weight of food items consumed by participants. 4,5,8,11,12 TFs of cooking medium i.e., oils and desi ghee were also calculated. After this, TFs of food items and cooking mediums were added and calories were calculated.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…The public at large does not have an opportunity to make informed choices which help in decreasing TFs intake as well as a decrease in health risk. 5 It is felt that there is an immediate need to make public aware of the ill-effects of TFs because India is home to the highest number of atherosclerosis cases in the world. 8 Importantly, in the Indian food-based dietary guidelines, guidelines for reducing TFs need to be included.…”
Section: Introductionmentioning
confidence: 99%